2012
DOI: 10.1002/ar.22452
|View full text |Cite
|
Sign up to set email alerts
|

Biometry and Statistical Analysis of the Styloid Process

Abstract: The hyoid apparatus is made up of three osteocartilaginous elements that go from the base of the cranium to the hyoid bone; the portions, cranially to caudally, are as follow: stylohyal, ceratohyal, and apohyal. Fusion and ossification of these three components will bring about somewhat long stylohyoid processes, whereas the stylohyal portion is the one that gives rise to the authentic stylohyoid process. The variability of the hyoid apparatus may imply associated compressive pathologies, for which an etiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In order to assess SP length, various imaging modalities, such as orthopantomograms (OPGs), lateral cephalometric radiographs [2,47], anteroposterior skull radiographs, computed tomography scanning [27,44] and anatomical methods utilising measurements in dry skulls [10,11,18,38,39,41,45,50] have been used. The advantage of metric studies in dry skulls is lack of distortion or superimpositions of structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess SP length, various imaging modalities, such as orthopantomograms (OPGs), lateral cephalometric radiographs [2,47], anteroposterior skull radiographs, computed tomography scanning [27,44] and anatomical methods utilising measurements in dry skulls [10,11,18,38,39,41,45,50] have been used. The advantage of metric studies in dry skulls is lack of distortion or superimpositions of structures.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of metric studies in dry skulls is lack of distortion or superimpositions of structures. On the other hand, it is rather hard to find numerous intact SPs, since SP is a particularly fragile part of the cranium [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thanuja et al, carried out a study with the same number of patients but with using a different method, found that the sagittal angulation was 80.6 degrees in males and 82.4 degrees in females, and the axial angulation was 25.2 degrees in males and 31.1 degrees in females. As a result, no statistically significant differences were found between the genders and the right / left side [26]. Crohn et al, found the mean styloid sagittal angle to be 56.7 degrees and a significant difference between males (63.4) and females (54.9) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variations of the hyoid-larynx complex occur in 4–30% of the general population 14 . Anomalies of this complex are of great importance for radiological examination and surgery of the neck region 1,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical variations of the hyoid-larynx complex occur in 4–30% of the general population 14 . Anomalies of this complex are of great importance for radiological examination and surgery of the neck region 1,5 . The significance of anomalies has also been well recognized in forensic sciences, as fractures in this complex are important indicators for strangulation and blunt or penetrating trauma on the neck 5–8 .…”
Section: Introductionmentioning
confidence: 99%